Perfil sensorial de cafés de cultivares em relação às faces de exposição das plantas e processamentos pós-colheita - Ribeiro, Bruno Batista (2014)
The present study was conducted with the objective of evaluating the sensorial quality of coffees from 6 cultivars, Coffea arabica. L., lapar 59, Paraíso MG H 419-1, Obatã IAC 1669-20, Catuaí Vermelho 144, Bourbon Amarelo and Topázio MG 1190, harvested from different exposure sides of the plants and submitted to two types of post-harvest processes. The natural and cherry with no mucilage coffees, after drying in suspended terrains, constituted of 100% mature fruits. The experiment was conducted in a private property in the municipality of Monte Carmelo, Minas Gerais, Brazil, Café do Cerrado region, during the 2011/2012 and 2012/2013 harvests. The location for the experiment’s execution was demarked, considering altitude, latitude and longitude, cultivation/management conditions, soil characteristics and age of the crops. The experimental design was based on the cultivars χ exposure sides χ post-harvest process characteristics, with three field replicates, combinations which resulted in 72 samples for each year. The sensorial analysis was performed according to the Specialty Coffee Association of America – SCAA (LINGLE, 2001) protocol with testers credentialed by the Coffee Quality Institute – CQI. The testers had better discrimination between the post-harvest processes of the coffees obtained in the sun side of the plants. The Obatã cultivar presented higher final grade between the evaluation years, and the Topázio provided better sensorial expression when dry processed, regardless of the exposure side. All cultivars presented potential for the production of special coffees with differences between the sensorial breaking point of the attributes and particularities of the nuances described by the SCAA protocol. The yellow fruit, Bourbon, Paraíso and Topázio cultivars, when submitted to dry processing, and obtained from the sun side of the plants, presented more elevated acidity, body and general attributes. Attributes such as yellow fruits, red fruits, chocolate and spices were perceptive among the different treatments studied which are highly valued and sought after in special coffees.